Prospects And Challenges of Global Governance: An Analysis of the Response by the International Community to the Ebola Outbreak in West Africa - Anderson, E. (University of Ghana, 2015)
The Ebola outbreak in West Africa has given a real test to Global Health Governance in recent times. This is due to its rapid geographic spread and negative global impact. Therefore, this study focuses on analyzing the prospects and challenges of Global Health Governance in relation to the international community‘s response to the Ebola outbreak in West Africa. The study covers the three most affected countries of the outbreak (i.e. Liberia, Sierra Leone and Guinea). The study covers the period from March, 2014 to July, 2015 in analyzing the international community‘s response to the pandemic. The study is purely qualitative and relies primarily on literature review and interviews for data collection and analyses. From the study, the international community‘s response to the Ebola outbreak in West Africa sheds light on some prospects and challenges confronting Global Health Governance. The prospects include the establishment of an independent mission; the United Nations Mission for Ebola Emergency Response (UNMEER) by the UN for the containment of the pandemic whilst a challenge includes the lack of leadership and non-existence of a recognized central coordination mechanism of Global Health Governance in effectively containing the pandemic. This resulted in about 11,000 deaths and drastic economic devastations, especially, in the most affected countries in West Africa. Following from the findings, the study concludes that, early securitization of the Ebola outbreak in West Africa would have mitigated the adverse cost of the drastic economic devastations and the over 11, 000 deaths recorded from the outbreak. Towards this end, the study recommends the need for the establishment of a more structured Multi-Lateral International Response Mechanism to provide quick and effective responses to future health crises. This can be achieved, if conscious efforts are taken by highest ranking personnel of Global Governance institutions to ensure that there is no delay in securitizing health threats in future.
MPhil. International Affairs
Keywords: Ebola outbreak; Global Health; Governance; United Nations; Pandemic